Japan : - Lu, David J. (M.E. Sharpe, 1997)
An updated edition of David Lu's acclaimed "Sources of Japanese History", this two volume book presents in a student-friendly format original Japanese documents from Japan's mythological beginnings through 1995. Covering the full spectrum of political, economic, diplomatic as well as cultural and intellectual history, this classroom resource offers insight not only into the past but also into Japan's contemporary civilisation. This volume covers up to the late 18th century. Three major criteria used in the document selection were that: the selection avoids duplication with other collections - 75% of the documents presented here are newly translated; a document accurately reflects the spirit of the times and the life-styles of the people; and emphasis is on the development of social, economic and political institutions.